1997
DOI: 10.1038/ki.1997.76
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin gene regulation depends on heme-dependent oxygen sensing and assembly of interacting transcription factors

Abstract: Studies on erythropoietin (Epo) gene expression have been useful in investigating the mechanism by which cells and tissues sense hypoxia. Both in vivo and in Hep3B cells. Epo production is induced not only by hypoxia but also by certain transition metal (cobalt and nickel) and by iron chelation. When Hep3B cells were incubated in an iron deficient medium, Epo mRNA expression was enhanced fourfold compared to Hep3B cells in iron enriched medium. Epo induction by cobalt was inversely related to iron concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 27 publications
1
42
0
1
Order By: Relevance
“…Under normal oxygen conditions, hydroxylation of Pro-402/564 located in the HIF-1␣ ODD allows for interaction of HIF-1␣ with the tumor suppressor protein VHL (19,20), whereas hydroxylation of Asn-803 prevents interaction of the C-terminal transactivation domain of HIF-1␣ with the CH1 pocket of the P300 protein (23). Exposure to nickel(II) or cobalt(II) results in accumulation of HIF-1␣ and up-regulation of hypoxia-inducible genes in cells even in the presence of oxygen (8,17,21,22). This phenomenon has been described as "metal-induced hypoxia" (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under normal oxygen conditions, hydroxylation of Pro-402/564 located in the HIF-1␣ ODD allows for interaction of HIF-1␣ with the tumor suppressor protein VHL (19,20), whereas hydroxylation of Asn-803 prevents interaction of the C-terminal transactivation domain of HIF-1␣ with the CH1 pocket of the P300 protein (23). Exposure to nickel(II) or cobalt(II) results in accumulation of HIF-1␣ and up-regulation of hypoxia-inducible genes in cells even in the presence of oxygen (8,17,21,22). This phenomenon has been described as "metal-induced hypoxia" (10).…”
Section: Discussionmentioning
confidence: 99%
“…Dimethyloxalylglycine (DMOG) was purchased from Frontier Scientific (Logan, UT). L- [1-14 C]Ascorbic acid (4.0 mCi/ mmol) was purchased from PerkinElmer Life Sciences, and L- [5][6][7][8][9][10][11][12][13][14] C]␣-ketoglutaric acid (50 mCi/mmol) was purchased from Moravek Biochemicals (Brea, CA).…”
Section: Methodsmentioning
confidence: 99%
“…The cooperative effects of HIF-1␣, HNF-4, and p300 appear to be similar as proposed for the EPO gene where, under hypoxia, heterodimeric HIF-1 binds to an HRE, while HNF-4 binds to a direct repeat downstream of the HRE. The binding of HNF-4 is crucial for an enhanced hypoxic response, and recruitment of the transcriptional coactivator p300 by HIF-1 and HNF-4 further enhanced the EPO expression (34,35).…”
Section: Involvement Of the Pi3k/pkb Pathway In The Regulation Of Genmentioning
confidence: 99%
“…So far, most of the studies on the effects of hypoxia on gene expression have focused on the induction of hypoxic genes and have not addressed the downregulation of aerobic genes. These studies on the induction of hypoxic genes have revealed that exposure to hypoxia can initiate a complex series of events, which begin with some sort of oxygen sensor and end with a signaling pathway that upregulates hypoxic genes (1,(5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%